Compositional and microstructural characterization of grave goods from Anta do Malhão and Soalheironas - Valério, Pedro (2019)
The technological features of the grave goods from Anta do Malhão and Soalheironas perfectly fit the metallurgical tradition of communities inhabiting the Southwestern Iberia during a period of transition from the 3rd to the 2nd millennium BC. Arsenical copper alloys began to be used for prestige goods of the 3rd millennium BC, becoming the standard for artefacts of the 2nd millennium BC, thus indicating the growing awareness of MBA metallurgists of the aesthetic and practical value of this silvery alloy.